Preparation method of pressureless sintered boron nitride composite ceramic
Through the pressure-free sintering technology and the uniform mixing of modified boron nitride whiskers and hexagonal boron nitride powder, the problems of complex equipment and high energy consumption during the sintering of existing hexagonal boron nitride ceramics are solved, and high efficiency and low cost are achieved The boron nitride composite ceramics are prepared with excellent mechanical properties and high purity.
Patent Information
- Application Number
- CN202411827239.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-14
AI Technical Summary
During the sintering process of existing hexagonal boron nitride ceramics, there are problems such as complex equipment, high energy consumption, low production efficiency and high production costs, and it is difficult to achieve large-scale industrial production.
Using pressure-free sintering technology, the modified boron nitride whiskers and modified hexagonal boron nitride powder are uniformly mixed, and cold isostatic molding is carried out, and inert gas or ammonia gas is introduced into the atmosphere furnace for high-temperature calcination. Boron nitride composite ceramic with excellent mechanical properties is produced.
It significantly improves the mechanical properties, sintering density and purity of composite ceramics, reduces production costs and energy consumption, and is suitable for large-scale industrial production.
Smart Images

Figure CN119430977A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic composite material preparation, and in particular to a method for preparing pressureless sintered boron nitride composite ceramic. Background Art
[0002] Hexagonal boron nitride (h-BN) is famous for its excellent thermal conductivity, insulation performance, high temperature stability, high temperature dielectric properties, excellent wave transmission performance, friction resistance and oxidation resistance. These characteristics make it widely concerned in high-tech fields such as aerospace and military industry. However, due to the low surface activity of hexagonal boron nitride and its covalent compound, it encounters great difficulties in the sintering process and is difficult to form dense ceramic materials. This problem limits the large-scale production and application of hexagonal boron nitride ceramics.
[0003] At present, the main preparation process of hexagonal boron nitride ceramics is completed by hot pressing sintering. Specifically, a vacuum hot pressing sintering furnace is used, and high pressure is applied during the sintering process to make the boron nitride particles in close contact and undergo solid-state diffusion, eventually forming a ceramic body with certain mechanical properties and density. In order to improve the sintering effect, inorganic materials such as alumina, aluminum nitride, silicon nitride, magnesium oxide, and yttrium oxide are usually added as sintering aids during the raw material mixing stage. Although this method can improve the mechanical properties of boron nitride ceramics to a certain extent, it also has obvious shortcomings: the required equipment is complex, the energy consumption is high, the production efficiency is low, and the production cost is high, all of which are not conducive to large-scale industrial production.
[0004] In recent years, with the growing demand for high-performance composite materials, boron nitride whiskers have entered people's field of vision as a new type of reinforcement material. Boron nitride whiskers are fiber materials generated in the form of single crystals. They have a tiny diameter, highly ordered internal atoms, and a strength close to the theoretical value of a complete crystal. In addition to inheriting the basic properties of hexagonal boron nitride, boron nitride whiskers also exhibit better high temperature resistance and corrosion resistance, as well as higher mechanical strength and electrical insulation. Therefore, introducing boron nitride whiskers as a reinforcement phase into the hexagonal boron nitride matrix can significantly improve the overall performance of the composite material, especially in improving the mechanical properties of the material.
[0005] However, the application of boron nitride whiskers in composite materials still faces many challenges. For example, the interface compatibility between boron nitride whiskers and matrix materials directly affects the final performance of the composite material, and how to optimize the interface structure to promote the effective combination between the two is one of the research focuses.
[0006] Therefore, an efficient and low-cost method is urgently needed to prepare boron nitride whiskers / hexagonal boron nitride composite ceramics with excellent mechanical properties to meet the needs of industrial applications. Summary of the invention
[0007] In view of the problems existing in the prior art, the present invention provides a method for preparing a pressureless sintered boron nitride composite ceramic, which not only overcomes the limitations of the traditional hot pressing sintering technology, but also significantly improves the comprehensive performance of the composite ceramic by introducing boron nitride whiskers as a reinforcement phase.
[0008] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing pressureless sintered boron nitride composite ceramics comprises the following steps:
[0010] (1) uniformly mixing the modified boron nitride whisker and the modified hexagonal boron nitride powder to obtain a mixture;
[0011] (2) placing the mixture into a cold pressing mold and performing cold isostatic pressing to obtain a cold pressed green body;
[0012] (3) The cold pressed green body is placed in an atmosphere furnace and an inert gas or ammonia gas is introduced for high-temperature calcination to obtain a boron nitride composite ceramic.
[0013] Furthermore, the preparation method of the modified boron nitride whisker comprises the following steps:
[0014] (a) adding boron nitride whiskers to an aqueous solution of ethanolamine and stirring the solution for a certain period of time;
[0015] (b) After the reaction is completed, the solid is filtered, dried, and sieved to obtain the modified boron nitride whiskers.
[0016] Furthermore, the aspect ratio of the boron nitride whisker is 20-80 μm.
[0017] Furthermore, the mass concentration of the ethanolamine aqueous solution is 20-50%.
[0018] Furthermore, the mass ratio of the boron nitride whiskers to the ethanolamine aqueous solution is 1:(3-10).
[0019] Furthermore, the stirring reaction is carried out at a temperature of 80-95° C. and for a time of 4-10 hours.
[0020] Furthermore, the screening is through a 40-100 mesh sieve.
[0021] Furthermore, the preparation method of the modified hexagonal boron nitride powder comprises the following steps:
[0022] (i) dispersing hexagonal boron nitride powder in an alkaline solution of a certain concentration and ball milling;
[0023] (ii) After the ball milling is completed, the solid is centrifuged, washed with water until neutral, dried, and sieved to obtain the modified hexagonal boron nitride powder.
[0024] Furthermore, the D50 particle size of the hexagonal boron nitride powder is 3-10 μm.
[0025] Furthermore, the alkaline solution is an aqueous solution of sodium hydroxide or potassium hydroxide with a mass concentration of 10-40%.
[0026] Furthermore, the mass ratio of the hexagonal boron nitride powder to the alkaline solution is 1:(5-15).
[0027] Furthermore, the rotation speed of the ball mill is 200-300 rpm, and the ball milling time is 4-8 hours.
[0028] Furthermore, the screening is through a 80-160 mesh sieve.
[0029] Adding modified boron nitride whiskers to the composite ceramic of the present invention can significantly improve the sintering activity of the material, improve the purity of the ceramic and the mechanical properties. The calcination temperature of boron nitride whiskers is 1100-1400°C, while the calcination temperature of hexagonal boron nitride powder is generally 1800-1900°C. This means that the activity of boron nitride whiskers is higher than that of hexagonal boron nitride powder. There are some hydroxyl groups on the surface of boron nitride whiskers. These hydroxyl groups can react with ethanolamine during the modification process to form stable BN covalent bonds. This modification not only improves the surface activity of the whiskers, but also makes it play an effective sintering aid role in the subsequent high-temperature calcination process. Due to the chemical composition of boron nitride whiskers, other impurity ions will not be introduced when they exist as a sintering aid. Therefore, the final boron nitride composite ceramic has high purity, which makes it suitable for many high-demand application scenarios, such as aerospace, military industry, etc. Boron nitride whiskers can play a crack bridging role in composite ceramics, that is, when the crack expands, the whiskers will prevent the crack from further expanding, thereby improving the fracture toughness of the ceramic; the presence of whiskers can deflect the crack during propagation, increase the length of the crack path, thereby consuming more energy and improving the material's crack resistance; when the crack expands, the whiskers can be pulled out of the matrix, and this process will also consume energy, further improving the material's toughness.
[0030] The present invention modifies hexagonal boron nitride, which is beneficial to enhancing interface compatibility and further improving mechanical properties. Through ball milling in an alkaline solution, some hydroxyl groups are generated on the surface of the hexagonal boron nitride powder. These hydroxyl groups can interact with the groups on the surface of the modified boron nitride whiskers during the subsequent high-temperature calcination process, and the interface compatibility between the two is significantly improved, which helps to form a more uniform and dense composite ceramic structure. The composite ceramic finally obtained has a higher density, thereby improving its mechanical properties, such as flexural strength and fracture toughness. In addition, the modified hexagonal boron nitride powder and boron nitride whiskers are easier to disperse evenly during the mixing process, avoiding local aggregation, and further improving the uniformity and overall performance of the composite ceramic.
[0031] The present invention adopts boron nitride whiskers as a reinforcing phase, which significantly improves the purity of the composite ceramic. In the traditional preparation process, sintering aids such as aluminum oxide and aluminum nitride are usually added to promote material densification, but these additives inevitably introduce additional impurity ions, affecting the purity and performance stability of the final product. In contrast, the present invention chemically modifies boron nitride whiskers and hexagonal boron nitride powder, utilizes the interface interaction between the two, and realizes an efficient sintering process without introducing any external sintering aids. After the surface of the boron nitride whisker is modified by ethanolamine, it can form a stable covalent bond with the hexagonal boron nitride powder, which not only enhances the interfacial bonding force, but also ensures the consistency and purity of the material composition. Therefore, the prepared boron nitride composite ceramic has extremely high purity, which helps to maintain the excellent physical and chemical properties inherent in the material, such as excellent thermal conductivity, electrical insulation and high temperature stability, while avoiding the problem of performance degradation caused by the presence of impurities, making the composite ceramic particularly suitable for application in fields with extremely high requirements for material purity, such as aerospace and high-end electronics industries.
[0032] Furthermore, in step (1), the mass ratio of the modified boron nitride whiskers to the modified hexagonal boron nitride powder is (2-3):10.
[0033] Furthermore, the cold isostatic pressing pressure in step (2) is 120-200 MPa, and the holding time is 80-120 s.
[0034] Furthermore, in step (3), the inert gas is one of nitrogen, argon and helium, and the calcination temperature is 1700-1900°C.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] 1. Improve the mechanical properties of boron nitride ceramics: By introducing modified boron nitride whiskers, the mechanical properties of composite ceramics, such as bending strength and flexural strength, are significantly improved.
[0037] 2. Improve the sintering density of boron nitride ceramics: The modification treatment improves the surface activity of boron nitride whiskers and hexagonal boron nitride powder, and promotes densification during the sintering process.
[0038] 3. High purity: Using modified boron nitride whiskers as the reinforcement phase avoids the introduction of other impurities and significantly improves the purity of the composite material.
[0039] 4. Reduce costs: The use of pressureless sintering technology reduces equipment requirements and energy consumption, and reduces production costs.
[0040] 5. Easy to mass produce: The entire preparation process is simple and controllable, suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is the SEM image of the boron nitride composite ceramic of Example 3.
[0042] Figure 2 This is the XRD pattern of the boron nitride composite ceramic of Example 3.
[0043] Figure 3 The force-deformation curves of the boron nitride composite ceramics of Example 3 are as follows: a. compressive strength curve; b. flexural strength curve.
[0044] Figure 4 The force-deformation curves of the boron nitride composite ceramic of Comparative Example 1 are as follows: a. compressive strength curve; b. flexural strength curve.
[0045] Figure 5 The force-deformation curves of the boron nitride composite ceramic of Comparative Example 2 are as follows: a. compressive strength curve; b. flexural strength curve.
[0046] Figure 6 The force-deformation curves of the boron nitride composite ceramic of Comparative Example 3 are as follows: a. compressive strength curve; b. flexural strength curve.
[0047] Figure 7 The force-deformation curves of the boron nitride composite ceramic of Comparative Example 4 are as follows: a. compressive strength curve; b. flexural strength curve. DETAILED DESCRIPTION
[0048] The technical scheme in the embodiment of the present invention will be clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.
[0049] Example 1
[0050] This embodiment provides a method for preparing modified boron nitride whiskers, comprising the following steps:
[0051] (a) Add 10 g of boron nitride whiskers to 50 g of a 30% aqueous solution of ethanolamine, heat to 90° C., and stir at constant temperature for 6 h;
[0052] (b) After the reaction is completed, the solid is filtered and dried in an oven at 60° C. The dried whiskers are sieved through a 60-mesh sieve to obtain the modified boron nitride whiskers.
[0053] Example 2
[0054] This embodiment provides a method for preparing modified hexagonal boron nitride powder, comprising the following steps:
[0055] (i) dispersing 10 g of hexagonal boron nitride powder in 100 g of 20% sodium hydroxide aqueous solution, placing the mixture in a ball mill, and milling the mixture at 200 rpm for 6 h;
[0056] (ii) After the ball milling is completed, the solid is centrifuged and repeatedly washed with pure water until the filtrate is neutral. The solid is dried and passed through a 100-mesh sieve to obtain the modified hexagonal boron nitride powder.
[0057] Example 3
[0058] This embodiment provides a method for preparing a pressureless sintered boron nitride composite ceramic, comprising the following steps:
[0059] (1) 20 g of the modified boron nitride whisker prepared in Example 1 and 100 g of the modified hexagonal boron nitride powder prepared in Example 2 were uniformly mixed to obtain a mixture;
[0060] (2) placing the mixture into a cold pressing mold and performing cold isostatic pressing to obtain a cold pressed green body, wherein the cold isostatic pressing pressure is 150 MPa and the holding time is 90 s;
[0061] (3) The cold pressed green body is placed in an atmosphere furnace, nitrogen is introduced, and the temperature is kept at 1850°C for 3 hours to obtain a boron nitride composite ceramic. The scanning electron microscope (SEM) image of the boron nitride composite ceramic is shown in FIG. Figure 1 As shown in the figure, it can be observed that fibrous boron nitride whiskers are uniformly dispersed in the hexagonal boron nitride powder matrix, forming an enhanced microstructure that helps to improve the mechanical properties of the material, such as flexural strength and compressive strength. Figure 2 shown.
[0062] Comparative Example 1
[0063] This comparative example provides a method for preparing a pressureless sintered boron nitride composite ceramic, which is different from Example 3 in that the boron nitride whiskers are not modified.
[0064] Comparative Example 2
[0065] This comparative example provides a method for preparing a pressureless sintered boron nitride composite ceramic, which is different from Example 3 in that the hexagonal boron nitride powder is not modified.
[0066] Comparative Example 3
[0067] This comparative example provides a method for preparing a pressureless sintered boron nitride composite ceramic, comprising the following steps:
[0068] (1) 20 g of boron nitride whiskers, 100 g of hexagonal boron nitride powder, and 10 g of sintering aid yttrium oxide were uniformly mixed to obtain a mixture;
[0069] (2) placing the mixture into a cold pressing mold and performing cold isostatic pressing to obtain a cold pressed green body, wherein the cold isostatic pressing pressure is 150 MPa and the holding time is 90 s;
[0070] (3) The cold-pressed green body is placed in an atmosphere furnace, nitrogen is introduced, and the temperature is kept at 1850° C. for 3 h to obtain a boron nitride composite ceramic.
[0071] Comparative Example 4
[0072] This comparative example provides a method for preparing a pressureless sintered boron nitride composite ceramic, which is different from Example 3 in that the method for preparing the modified boron nitride whisker comprises the following steps:
[0073] (a) Add 10 g of boron nitride whiskers to 50 g of a 30% aqueous solution of ethylenediamine, heat to 90° C., and stir at constant temperature for 6 h;
[0074] (b) After the reaction is completed, the solid is filtered and dried in an oven at 60° C. The dried whiskers are sieved through a 60-mesh sieve to obtain the modified boron nitride whiskers;
[0075] The modified boron nitride whiskers prepared as above are used to prepare boron nitride composite ceramics. The preparation method of the boron nitride composite ceramics is the same as that of Example 3.
[0076] Performance Testing
[0077] The compressive strength and flexural strength of the boron nitride composite ceramics prepared in Example 3 and Comparative Examples 1-4 were tested. The compressive strength was tested according to GB / T 8489-2006, and the flexural strength was tested according to GB / T 6569-2006. The test samples were prepared according to the corresponding national standards, and the sample test curves were as follows: Figure 3-7As shown, the flexural strength and compressive strength of the samples were calculated according to the method specified in the national standard, and the results are shown in Table 1.
[0078] Table 1:
[0079] sample Flexural strength(MPa) Compressive strength(MPa) Example 3 106.7 126.03 Comparative Example 1 98 109.2 Comparative Example 2 40.7 87.59 Comparative Example 3 35.7 46.89 Comparative Example 4 22 42
[0080] The above results show that the boron nitride composite ceramics prepared by the present invention have excellent compressive strength and flexural strength. Comparative Example 1 did not modify the boron nitride whiskers, resulting in weak bonding between the whiskers and the matrix, affecting the mechanical properties. Comparative Example 2 did not modify the hexagonal boron nitride powder, affecting its activity during the sintering process and bonding with the whiskers, thereby affecting the mechanical properties. Comparative Example 3 did not modify the boron nitride whiskers and hexagonal boron nitride, but added yttrium oxide as a sintering aid. Although the addition of the sintering aid can enhance the mechanical properties of the material, its mechanical properties are still significantly lower than those of the solution of the present invention. In addition, the addition of the sintering aid will introduce impurities, affecting the purity and mechanical properties of the material. Comparative Example 4 changed the modification method of the boron nitride whiskers, proving that the effect of modifying the boron nitride whiskers with ethylenediamine is not ideal.
[0081] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a pressureless sintered boron nitride composite ceramic, comprising the following steps; (1) uniformly mixing the modified boron nitride whisker and the modified hexagonal boron nitride powder to obtain a mixture; (2) placing the mixture into a cold pressing mold and performing cold isostatic pressing to obtain a cold pressed green body; (3) placing the cold pressed green body into an atmosphere furnace, introducing an inert gas or ammonia gas, and calcining the green body to obtain the pressureless sintered boron nitride composite ceramic; in, The preparation method of the modified boron nitride whisker comprises the following steps: (a) adding boron nitride whiskers to an aqueous solution of ethanolamine and stirring the solution for a certain period of time; (b) After the reaction is completed, the solid is filtered, dried, and sieved to obtain the modified boron nitride whiskers; The preparation method of the modified hexagonal boron nitride powder comprises the following steps: (i) dispersing hexagonal boron nitride powder in an alkaline solution of a certain concentration and ball milling; (ii) After the ball milling is completed, the solid is centrifuged, washed with water until neutral, dried, and sieved to obtain the modified hexagonal boron nitride powder.
2. The preparation method according to claim 1, characterized in that: The aspect ratio of the boron nitride whisker in step (a) is 20-80 μm, and the mass concentration of the ethanolamine aqueous solution is 20-50%.
3. The preparation method according to claim 1, characterized in that: The mass ratio of the boron nitride whisker to the ethanolamine aqueous solution in step (a) is 1:(3-10).
4. The preparation method according to claim 1, characterized in that: The stirring reaction in step (a) is carried out at a temperature of 80-95° C. for 4-10 hours; and the sieving in step (b) is carried out through a 40-100 mesh sieve.
5. The preparation method according to claim 1, characterized in that: The D50 particle size of the hexagonal boron nitride powder in step (i) is 3-10 μm, and the alkaline solution is an aqueous solution of sodium hydroxide or potassium hydroxide with a mass concentration of 10-40%.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the hexagonal boron nitride powder to the alkaline solution in step (i) is 1:(5-15).
7. The preparation method according to claim 1, characterized in that: The rotation speed of the ball mill in step (i) is 200-300 rpm, the ball milling time is 4-8 hours, and the sieving in step (ii) is 80-160 mesh sieve.
8. The preparation method according to claim 1, characterized in that: The mass ratio of the modified boron nitride whiskers to the modified hexagonal boron nitride powder in step (1) is (2-3):
10.
9. The preparation method according to claim 1, characterized in that: The cold isostatic pressing pressure in step (2) is 120-200 MPa, and the holding time is 80-120 s.
10. The preparation method according to claim 1, characterized in that: In step (3), the inert gas is one of nitrogen, argon and helium, and the calcination temperature is 1700-1900°C.
Citation Information
Cited By
High-strength and high-deformability hexagonal boron nitride ceramic and preparation method thereof
CN118771892A
High-strength high-deformation hexagonal boron nitride ceramic and method for preparing the same
CN118771892B